Exploring additive and non-additive genetic models to decipher the genetic regulation of almond tolerance to Diaporthe amygdali - Catalano, Chiara; Gusella, Giorgio; Inzirillo, Ilaria; Cannizzaro, Giuseppe; Di Guardo, Mario; La Malfa, Stefano; Polizzi, Giancarlo; Gentile, Alessandra; Distefano, Gaetano (Frontiers in Plant Science, 2025)
Constriction canker (Diaporthe amygdali) is one of the main diseases affecting almond cultivation. To unravel the genetic basis of the tolerance to the disease, a germplasm collection of 123 almond accessions (111 selected in Sicily, Italy, complemented with widely cultivated Italian and International varieties), was employed for a Genome-Wide Association Study (GWAS). Accessions were phenotyped employing a detached-twig inoculation assay, here employed for the first time for a GWAS, ensuring high throughputness and reproducibility. The most susceptible and tolerant accessions were also inoculated in planta and the two phenotyping methods showed a significant correlation of 0.7. Genotyping was performed using the Axiom™ 60K almond array, resulting in the identification of 47,496 robust markers. Both additive and non-additive GWAS models were tested leading to the identification of nine SNPs significantly associated with tolerance to D. amygdali. Candidate genes in linkage-disequilibrium with the significant SNPs were functionally characterized and a subset of 20 were further validated through RT-qPCR in both the most tolerant (the Sicilian ‘Cuti’) and susceptible (‘Ferraduel’) genotypes at 0 and at 2 days after in planta inoculations. The results provide novel insights to understand the genetic regulation of the tolerance to D. amygdali and for the set-up of marker-assisted selection plans in almond.